(untitled) (Web of Teachers: Inderscience Research, 2025)
This article presents a comprehensive review of the role of independent study in fostering English for Specific Purposes (ESP) proficiency and enhancing learner autonomy among students in higher education. Drawing upon contemporary scholarly literature, it elucidates the theoretical underpinnings of self-directed learning within the ESP context and examines its pedagogical benefits, associated challenges, and technological facilitators. The review synthesizes findings on effective strategies for integrating independent study, including the strategic use of Artificial Intelligence (AI) and Mobile-Assisted Language Learning (MALL). It discusses the evolving role of educators in promoting learner autonomy and identifies areas for future research.